Financial Performance Analysis Before and During the Covid-19 pandemic (Case Study on Telecommunication Companies 2017-2022) - hidayat, solikhul; Nur Safitri, Fadillah (Jurnal Rekognisi Akuntansi, 2024)
This research aims to find out: (1) How the net profit margin differs in telecommunications companies before and during the Covid-19 pandemic (2) How the current ratio differs in telecommunications companies before and during the Covid-19 pandemic (3) How the debt to equity ratio differs in telecommunications companies before and during the Covid-19 pandemic (4) and what are the differences in total asset turnover in telecommunications companies before and during the Covid-19 pandemic. This research used a qualitative descriptive method and the sampling technique was carried out by means of purpose sampling so that a sample of 17 telecommunications companies was obtained. The data used are telecommunications company financial reports for 2017-2022. The research uses secondary company data and utilizes analysis techniques with the Wilcoxon test. To determine the normality of the data, a normality test (One-Sample Kolmogorov-Smirnov Test) and Descriptive Statistics Test were used. The results of this research show that based on the net profit margin ratio, debt to equity ratio in telecommunications companies between before and during Covid-19 there was no difference, only total asset turnover showed a difference between before and during Covid-19.